(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Concha bullosa is a common anatomical variation, yet its mechanical and pathological impact on the ostiomeatal complex remains controversial. Objectives: To determine the prevalence of concha bullosa and analyze its association with maxillary ostium stenosis and maxillary sinusitis on computed tomography (CT). Subjects and Methods: A cross-sectional descriptive study was conducted on 170 patients (corresponding to 340 nasal sides) who underwent sinonasal computed tomography at Nhan Dan Gia Dinh Hospital from June 2024 to June 2025. Maxillary sinusitis on CT was defined as mucosal thickening >2 mm or partial/complete sinus opacification according to the Lund-Mackay system. Results: Concha bullosa was observed in 39.4% of the surveyed sides. Morphologically, the group with concha bullosa showed a trend toward a higher rate of maxillary ostium stenosis (8.7%) compared to the group without it (4.6%) (OR = 1.98); however, this difference was not statistically significant (p = 0.284). Pathologically, the prevalence of maxillary sinusitis on CT in the concha bullosa group (38.8%) was significantly lower than in the non-concha bullosa group (55.3%) (p = 0.018; OR = 0.51). Conclusion: Concha bullosa shows a tendency towards anatomic narrowing of the maxillary ostium due to mechanical compression, but demonstrates an inverse correlation with maxillary sinusitis on CT. These findings suggest that concha bullosa alone is not associated with an increased prevalence of maxillary sinusitis on CT in this sample.